Histopathological Spectrum and Immunohistochemical Profile of Lung Carcinomas: A 9-Year Study from a Tertiary Hospital in North India - Bhatti, Vandana (Int J Appl Basic Med Res, 2019)
BACKGROUND: Lung cancer is the most common cancer worldwide and the leading cause of cancer-related death. Diagnostic bronchoscopic or percutaneous biopsies are usually small. However, judicious use of immunohistochemistry (IHC) helps in accurate subtyping, which forms the basis for molecular tests and treatment. AIM: The aim was to study the role of IHC in the diagnosis of various histological subtypes of lung cancer. METHODS: This 9-year study from 2009 to 2017 included all cases diagnosed as lung carcinoma on tissue biopsies. IHC markers were selected based on histopathology, from a panel comprising CK7, CK20, CK5/6, p63, thyroid transcription factor 1 (TTF-1), napsin A, synaptophysin, chromogranin A, neuron-specific enolase, CD56, and CDX2. Metastatic cancers to the lung were excluded from the study. RESULTS: There were 199 cases of lung carcinoma comprising squamous cell carcinoma (37.7% [n = 75]), adenocarcinoma (26.1% [n = 52]), small cell carcinoma (20.6% [n = 41]), non-small cell lung carcinoma-unclassified (10.1% [n = 20]), adenosquamous carcinoma (2.5% [n = 5]), and others (3% [n = 6]). IHC was done on 47.7% (95/199) of cases. Squamous cell carcinomas showed CK5/6 and p63 positivity in 13/13 (100%) and 12/13 (92.3%) cases, respectively. Adenocarcinomas were positive for napsin A in 12/13 (92.3%) and TTF-1 in 35/41 (85.4%) cases. Neuroendocrine markers were positive in all small cell carcinomas. CONCLUSION: Squamous cell carcinoma was the most common primary lung malignancy in the North Indian population, followed by adenocarcinoma and small cell carcinoma. IHC panel of TTF-1, napsin A, CK5/6, and p63 is very helpful to classify most non-small cell lung carcinomas.